The effect of use of information technology, human resource competency and internal control systems on the quality of regional financial reports (Study on Bangkalan Regency Regional Apparatur Organizations) - Kartika Rusnindita; Rachmad Hidayat (Technium Social Sciences Journal, 2023)
The quality of financial statements is said to be good if in the report the information presented can be understood and meet the needs of its users in decision making, does not provide a distorted understanding, and also material errors, but presents reliable financial statements, so that from previous periods the financial statements can be compared clearly and accurately. The purpose of this study is to examine the influence of variables in the use of information technology, human resources and internal control systems on the quality of regional financial statements. The population in this study was 9,494 government devices located in 33 Regional Apparatur Organizations of Bangkalan Regency. The sampling technique uses purposive sampling technique, so that a sample of 99 respondents is obtained, which will be given a questionnaire to be filled out. The data analysis technique uses multiple linear regreation analysis. The results of this study prove that partially the use of information technology and internal control systems has a significant effect on the quality of regional financial statements. Meanwhile, human resources do not affect the quality of regional financial statements. The results of simultaneous analysis show that the use of information technology, human resources and internal control systems has a significant effect on the quality of regional financial statements.